PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH DAN JUMLAH PENDUDUK TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN MAGELANG TAHUN 2009-2018 - Ika Puspita Nugraheni; Rusmijati .; Lucia Rita Indrawati (Universitas Tidar, 2020)
The purpose of this study was to determine and analyze the influence of local taxes, localretributions and the number of populationagainst District Own Source Revenue (DOSR) in2009-2018 period. The data of this study are local taxes, local retributions, the number ofpopulation, and District Own Source Revenueof Magelang Regency in the 2009-2018 period.This research data collection technique uses the method of literature and research data issecondary data. The data analysis technique of this study used multiple linear regressionanalysis, F test and t test. The results of this study indicate that the simultaneous local taxes,local retributions and the number of population affect the District Own Source Revenue witha percentage of influence of 95.6%. Partially, local taxeshas a significant positive effect onDistrict Own Source Revenue, while local retributions and the number of population do notaffect District Own Source Revenue.